Effectiveness of Semont maneuver in the treatment of benign paroxysmal positional vertigo: an institutional study - U. P., Swapna; B., Smitha; Kumar K., Salil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Benign paroxysmal positional vertigo (BPPV) is a common cause of vertigo. In this condition, the vertigo is precipitated by certain head movements. BPPV is diagnosed by Dix-Hallpike positional test. Various repositioning maneuvers and treatment modalities exist for the management of this condition. Semont maneuver is a simple procedure for the treatment of posterior semicircular canal BPPV. Methods: This non randomized controlled study was conducted in the ENT Department of a tertiary care hospital at Thiruvananthapuram over a period of one year. Hundred patients with posterior semicircular canal BPPV were included in the study. Fifty patients treated with Semont maneuver were compared with 50 patients who were treated with betahistine 16 mg three times daily. Outcomes were measured by relief of vertigo and negative Dix- Hallpike positional test during follow up examination. Results: The most common age group affected by BPPV was 50-60 years. Right side was more affected than the left. There was a female preponderance. 84% patients treated with Semont maneuver were cured at the end of the first week and 90% at the end of the second week. The percentage of patients cured with betahistine were 48% at the end of first week and 56% at the end of second week. Conclusions: The Semont maneuver was very effective in the treatment of BPPV. It helps to reduce the long-term use of medicines in our population.